Novel Flavivirus Attenuation Markers Identified in the Envelope Protein of Alfuy Virus - Daniel Westlake; Helle Bielefeldt-Ohmann; Natalie A. Prow; Roy A. Hall (Viruses, 2021)
Alfuy (ALFV) is an attenuated flavivirus related to the Murray Valley encephalitis virus (MVEV). We previously identified markers of attenuation in the envelope (E) protein of the prototype strain (ALFV3929), including the hinge region (E273–277) and lack of glycosylation at E154-156. To further determine the mechanisms of attenuation we assessed ALFV3929 binding to glycosaminoglycans (GAG), a known mechanism of flaviviruses attenuation. Indeed, ALFV3929 exhibited reduced binding to GAG-rich cells in the presence of heparin; however, low-passage ALFV isolates were relatively unaffected. Sequence comparisons between ALFV strains and structural modelling incriminated a positively-charged residue (K327) in ALFV3929 as a GAG-binding motif. Substitution of this residue to the corresponding uncharged residue in MVEV (L), using a previously described chimeric virus containing the prM & E genes of ALFV3929 in the backbone of MVEV (MVEV/ALFV-prME), confirmed a role for K327 in enhanced GAG binding. When the wild type residues at E327, E273–277 and E154–156 of ALFV3929 were replaced with the corresponding residues from virulent MVEV, it revealed each motif contributed to attenuation of ALFV3929, with the E327/E273–277 combination most dominant. These data demonstrate that attenuation of ALFV3929 is multifactorial and provide new insights for the rational design of attenuated flavivirus vaccines.